Deploying Discourses of Employability and Domesticity: Women's Employment and Training Policies and the Formation of the Canadian Welfare State, 1935–1947 - Stephen, Jennifer Anne (University of Toronto, Ontario Institute for Studies in Education, 2000)
The period 1935 to 1947 provides an excellent opportunity to investigate the ways in which the employment and training policies of Canadian welfare state forms delineated the boundaries of gender, race, class and nation in ways that actively constituted (il)legitimate social and economic forms of work, of motherhood, of sexuality and citizenship. Covering attempts starting in the Depression and accelerating during the Second World War into the postwar period, this study tracks the constitution and deployment of government attempts at mapping the female labour supply, of monitoring the activities of women in the labour market, of charting and opening up to scrutiny the conditions of women's labour force attachment: all in an effort to predict and prescribe patterns of women's employment and problems of female unemployment. I approach government reports, studies, commissions and committees as policy events—exercises in governance—as markers for policy analysis which signified important shifts in governmental approaches to the phenomenon of female participation in the formal waged economy. Viewed during the war as a crucial national resource, central to the war effort, women war workers would be cast as a largely ‘unskilled female labour reserve’ by war's end. I examine how ideas about mental testing, intelligence and human capacities—ideas that comprised the foundation of the mental hygiene programme during this period—informed employment and training policies in the formation of the Canadian welfare state for the period 1935–1947. During the Depression, studies of the labour force produced classifications of unemployed women and men. Scrutiny of female employment patterns resulted in the production of categorical knowledges about employability. These practices were further elaborated through the unprecedented research opportunities presented by the war. Suitable vocation, aptitude, and measures of intelligence: these concepts were drawn upon as part of a growing apparatus of employment policy intended to facilitate the smooth transition into the postwar period. I argue that the roster of policies and programmes devised in the name of postwar rehabilitation constituted ideas about female employability which were deeply imbued with the principles of scientific racism and sexism at the core of the mental hygiene program. Vocational planning, counselling and training practices reorganised relations of employment and of unemployment in ways that reflected the managing principles of the risk society. Postwar planning drew upon and constituted new areas of activity for government and community agencies, creating opportunities for the deployment of knowledge-practices such as personnel selection while opening up the interior of the subject as an object of governance, by assessing and calibrating allegedly innate human capacities.
Keywords: Domesticity; Education; Employment and training policies; Social sciences; Welfare state; Women